IJTIHÃD ISTINBÃT DAN IJTIHÃD TATBÃQI MENURUT AL-SYÃTIBÃ DALAM KITÃB AL-MUWAFAQÃT - Fatimah, Fatimah (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
This article outlines the problems and tatbiqi istinbati ijtihad according to al-Syatibi in the book of al-Muwafaqât. From the results of the discussion is known that; Ijtihad is an attempt to think optimally in multiplying laws of the source for answers to legal issues that arise in society. Istinbâti Ijtihad is an effort to conclude the law of his sources (legal excavation efforts of the sacred texts). While ijtihad tatbîqi is an attempt to apply the law appropriately to a case (attempt to apply the law that was unearthed from the sacred texts to the object of law). According to al-Mujtahid Syatibi should not apply the law that has been excavated from the Quran or the Sunna as it is, he is obliged to give consideration based on the circumstances surrounding the object of the law. Wherever the law resulting from his ijtihad is not suitable to be applied to the object of law because the application of laws that bring harm, then the mujtahid must find other, more appropriate laws so that harm can be eliminated and the benefit can be achieved.